Efficacy of the Fumigant Ethanedinitrile to Control the Ham Mite, Tyrophagus putrescentiae (Schrank) (Sarcoptiformes: Acaridae), and Its Sorption on Dry-Cured Ham - Jacqueline M. Maille; Wes Schilling; Thomas W. Phillips (Insects)
Management of stored-product pests has historically relied on fumigation when pest populations become large. However, the ban of the fumigant methyl bromide and the ineffectiveness of other pesticides stress the need for alternative fumigants. Therefore, laboratory studies were conducted to evaluate the efficacy of ethanedinitrile (EDN) against different life stages of the mite Tyrophagus putrescentiae and to determine the sorption and desorption of EDN by dry-cured ham meat. The results showed that eggs were the most tolerant life stage to EDN fumigation, with an estimated LC50 of 0.6 mg/L. Tyrophagus putrescentiae mixed life-stage colonies were controlled at 1.3 mg/L, and less than 0.05% of the population survived following treatment with 0.6 mg/L within 24 h at 25 °C. The free-headspace concentrations of EDN in fumigation chambers containing ham decreased by 97% of the initial concentrations applied (2.6 and 4.8 mg/L) after the 24 h fumigation period. The EDN sorption in ham followed the first-order kinetics, with half-life values of 5.0 and 4.9 h for 2.6 and 4.8 mg/L, respectively. The percentage losses of EDN per hour were calculated to be 12.8 and 13.2% at 2.6 and 4.8 mg/L, respectively. Our study indicates that EDN controls T. putrescentiae in the laboratory.